The Development of Poetry Reading Media Learning Through Digital Literation - Syafrial, Syafrial; Rumadi, Hadi; Rasdana, Oki (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is based on the recommendation of literacy in schools by ministries as well as the advancement of digital technology that is able to provide new innovations for learning in particular in this case learning to read poetry. This research method uses Research and Development method with observation, interview, questionnaire, and documentation data collection techniques and quantitative and qualitative data analysis techniques. The results of this study in the form of learning products to read poetry begins with reading each verse verses up to the whole verse verse. The recitation of the poem is sung using the tone of selendang delima, dodoi, dan surat kapal. This media will guide students and teachers in learning to read poetry well and correctly and equipped with practice. Through this media, it is hoped that it can help to make it easier to convey learning messages in reading poetry. In addition, the virtue of poetry is able to correctly remember, so that the representation of values contained in the poem remains intact. The author hopes that this learning media will make students practice, think actively and critically in understanding poetry reading.